THE INTEGRATION OF PROJECT-BASED LEARNING (PBL) IN EDUCATION 4.0 TOWARD EFL STUDENTS’ ACTIVITIES - Helsa Gita Almaida; Alan Jaelani (ENGLISH, 2021)
This research aims to realize the implementation and integrated project-based learning (PBL) activities in education 4.0 towards EFL students’ activities. This study uses qualitative methods as a framework for analyzing and collecting data. The data were obtained from observations and interviews. The results showed that the use of Google Classroom, Comic Page Creator, and Learning Apps can complement projects in the EFL class; the use of Google Classroom, Comic Page Creator, and Learning Apps can help students access the material and complete the Project; and most students integrating PBL into Education 4.0 can improve their English language skills.